A Numerical Approach for 3 PRS Parallel Manipulator - Selvakumar A, Arockia; ., . (International Journal of Engineering and Technology, 2018)
This paper presents a numerical approach on kinematic analysis of 3-DOF parallel manipulator (PM). The proposed mechanisms constitute of PRS (Prismatic-Revolute-Spherical) parallel mechanism with two rotations and one translation. The forward and inverse kinematic equations of the PM are derived by position vector method. A total of 48 solutions are obtained for the forward kinematic equations using MATLAB.Â